Dampak Program Padat Karya Tunai Desa (Cash-for-Work) terhadap Kriminalitas Desa di Jawa Timur - Sabrina, Bella M; Purwanti, Evi Y (Jurnal Kebijakan Ekonomi, 2025)
High crime rates in rural areas indicate development inequality and low welfare. The government initiated the Padat Karya Tunai Desa Program (Cash-for-Work) to improve welfare by providing employment. Using the Difference-in-Difference method with 2018 and 2021 PODES data from 7,721 villages in East Java, this study analyzes the impact of the PKTD Program and socio-economic factors on crime using three measures: total crime types, theft, and violence. Results show that the Cash-for-Work program does not reduce total crime types and violence, but has the potential to reduce theft. The number of poor-family increases crime, while the number of micro-industries reduces crime.